Behavioral Factors Influencing Peer-to-Peer Lending Usage: A Systematic Literature Review from the Perspective of Indonesian Borrowers' Needs - Febriana, Mazaya (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This systematic literature review (SLR) investigates behavioral factors affecting peer-to-peer (P2P) lending adoption from Indonesian borrowers' financial needs viewpoint. Utilizing a descriptive qualitative approach with PRISMA guidelines, literature was retrieved through Publish or Perish with keywords "peer-to-peer," "lending," and "Indonesia" spanning 2020–2025, resulting in 169 articles narrowed to 42 via Rayyan screening based on criteria like peer-review, language, and accessibility. The inductive analysis of variables including usefulness, risk, and trust across studies on Java and rural UMKM borrowers reveals that perceived usefulness and ease of use facilitate efficient funding during crises like COVID-19. Trust reduces risks in syariah-compliant platforms, and social influence accelerates rural uptake, though persistent defaults highlight regulatory gaps. Implications emphasize strengthened OJK supervision for secure platforms to advance sustainable inclusion, countering overly positive economic models and proposing enhancements such as AI ethics integration. Future research should involve empirical longitudinal studies across ASEAN using mixed-methods to confirm factors and assess cross-cultural impacts.